Kolaborasi Guru Dan Peserta Didik Dalam Membangun Disiplin Positif di SMA Negeri 5 Kupang - Irvantus Jebagun (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2025)
This study aims to find out: 1) the collaboration of teachers and students in building positive discipline at SMA Negeri 5 Kupang. 2) the factors that inhibit the collaboration of teachers and students in building positive discipline at SMA Negeri 5 Kupang. The type of research uses qualitative methods. The subjects in this study are teachers and students. Data collection techniques through observation, interviews, and documentation and data analysis techniques used are data collection, data reduction, data presentation and conclusions. The results of this study show that: the collaboration of teachers and students in building positive discipline at SMA Negeri 5 Kupang is in the form of 1) mutual trust, 2) mutual respect, 3) mutual care, and 4) mutual reinforcement. The factors that hinder teacher and student collaboration in building positive discipline at SMA Negeri 5 Kupang are: 1) not being responsible for their duties, 2) lacking confidence, 3) often seeking attention from others, and 4) often lying as an excuse for coming to school late.